2019
DOI: 10.3324/haematol.2018.211011
|View full text |Cite
|
Sign up to set email alerts
|

The novel CD19-targeting antibody-drug conjugate huB4-DGN462 shows improved anti-tumor activity compared to SAR3419 in CD19-positive lymphoma and leukemia models

Abstract: Antibody-drug conjugates (ADC) are a novel way to deliver potent cytotoxic compounds to cells expressing a specific antigen. Four ADC targeting CD19, including SAR3419 (coltuximab ravtansine), have entered clinical development. Here, we present huB4-DGN462, a novel ADC based on the SAR3419 anti-CD19 antibody linked via sulfo-SPDB to the potent DNA-alkylating agent DGN462. huB4-DGN462 had improved in vitro anti-proliferative and cytotoxic activity compared to SAR341… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…[3][4][5]12 However, previous data do not demonstrate that the use of IMT increases the risk of other viral pneumonias, such as influenza. 17 Therefore, statement B is also correct. Yet it is known that in  Figure 3.…”
Section: Covid-19 Risk In Cancer Patients Receiving Immunotherapymentioning
confidence: 92%
“…[3][4][5]12 However, previous data do not demonstrate that the use of IMT increases the risk of other viral pneumonias, such as influenza. 17 Therefore, statement B is also correct. Yet it is known that in  Figure 3.…”
Section: Covid-19 Risk In Cancer Patients Receiving Immunotherapymentioning
confidence: 92%
“…Based on vitro and vivo B cell malignancy study report, the novel CD19 targeting antibody drug conjugate hub4-dgn462 showed significant improvements in anti-tumor activity CD19-positive lymphoma-leukemia models .This would provide a best option for the near future of B cell malignancy therapy using antibody drug conjugates [69].…”
Section: Naked Antibodies Bispecific Antibodies and Conjugated Antibmentioning
confidence: 98%
“…116 A novel ADC based on coltuximab ravtansine showed promising preclinical data and may become an attractive candidate for clinical investigation. 117 Loncastuximab tesirine (ADCT-402) is a novel CD19-targeted ADC that delivers SG3199, a highly cytotoxic pyrrolobenzodiazepine dimer, and showed highly targeted cytotoxicity in vitro and antitumor activity in vivo in preclinical studies. 118 A pivotal phase 2 study (NCT03589469) is currently ongoing on relapsed or refractory DLBCL, as well as phase 1 studies (NCT02669017, NCT03684694, and NCT03685344) on relapsed or refractory B-NHLs.…”
Section: Cd19mentioning
confidence: 99%